Hedging Strategy in Petro Summit - Is It Effective? - Lee, Chee Kong (2010)
This paper attempts to find out the hedging strategy of Petro Summit and explore its effectiveness. Was the income volatility due to some risks that cannot be hedged and that it is masking the effectiveness of the hedging strategy in Petro Summit? Could the company have done better in hedging their risks (i.e. was the hedging in Petro Summit effective)?